The college students' engagement motivations in hot topics on social media: a study based on Q-method from China - Zhang, Ziqi; Huang, Yangsen (Frontiers in Psychology, 2025)
In the era of mobile internet, college students demonstrate significant enthusiasm for participating in discussions of hot topics on social media platforms. Existing research indicates that this engagement is driven by a variety of internal and external factors, including self-efficacy, psychological empowerment, and the influence of new media technologies. Despite these insights, there remains a scarcity of in-depth studies focusing on the primary motivations behind such behavior, particularly regarding individual differences among students. To address this gap, the present study employs Q methodology—a mixed-method approach combining qualitative and quantitative techniques—to systematically analyze the subjective motivations of college students engaging in online trending topics. Through the analysis of participants' sorting of statement cards and subsequent factor extraction, four distinct engagement profiles were identified: self-referential rationalists, who prioritize practical benefits; values-driven advocates, who are driven by moral and social principles; interest-oriented participants, who seek to share personal opinions; and rights-protection oriented participants, who engage in discourse to protect their pre-existing views or group interests. These findings offer valuable insights for digital citizenship education, student support services, and media literacy programming. Rather than applying uniform approaches, educators and platform designers could develop tailored strategies that acknowledge these varied motivational profiles.